Functional Outcomes and Their Association With Physical Performance in Mechanically Ventilated Coronavirus Disease 2019 Survivors at 3 Months Following Hospital Discharge: A Cohort Study. Issue 10 (October 2021) - van Gassel, Rob J. J.; Bels, Julia; Remij, Loes; van Bussel, Bas C. T.; Posthuma, Rein; Gietema, Hester A.; Verbunt, Jeanine; van der Horst, Iwan C. C.; Olde Damink, Steven W. M.; van Santen, Susanne; van de Poll, Marcel C. G.
Abstract : OBJECTIVES: We performed a comprehensive health assessment in mechanically ventilated coronavirus disease 2019 survivors to assess the impact of respiratory and skeletal muscle injury sustained during ICU stay on physical performance at 3 months following hospital discharge. DESIGN: Preregistered prospective observational cohort study. SETTING: University hospital ICU. PATIENTS: All mechanically ventilated coronavirus disease 2019 patients admitted to our ICU during the first European pandemic wave. MEASUREMENTS AND MAIN RESULTS: At 3 months after hospital discharge, 46 survivors underwent a comprehensive physical assessment (6-min walking distance, Medical Research Council sum score and handgrip strength), a full pulmonary function test, and a chest CT scan which was used to analyze skeletal muscle architecture. In addition, patient-reported outcomes measures were collected. Physical performance assessed by 6-minute walking distance was below 80% of predicted in 48% of patients. Patients with impaired physical performance had more muscle weakness (Medical Research Council sum score 53 [51–56] vs 59 [56–60]; p < 0.001), lower lung diffusing capacity (54% [44–66%] vs 68% of predicted [61–72% of predicted]; p = 0.002), and higher intermuscular adipose tissue area ( p = 0.037). Reduced lung diffusing capacity and increased intermuscular adipose tissue were independently associated with physical performance. CONCLUSIONS: Physical disability is common at 3 months in severe coronavirus disease 2019 survivors. Lung diffusing capacity and intermuscular adipose tissue assessed on CT were independently associated with walking distance, suggesting a key role for pulmonary function and muscle quality in functional disability. Abstract : Supplemental Digital Content is available in the text.